A generalized theory of electrical characteristics of schottky barriers for amorphous materials - Gupta, H. M. [UNESP] (Wiley, 1997)
In the present paper, we discuss a generalized theory of electrical characteristics for amorphous semiconductor (or insulator) Schottky barriers, considering: (i) surface states, (ii) doping impurity states at a single energy level and (iii) energetically distributed bulk impurity states. We also consider a thin oxide layer (≈10 Å) between metal and semiconductor. We develop current versus applied potential characteristics considering the variation of the Fermi level very close to contact inside the semiconductor and decrease in barrier height due to the image force effect as well as potential fall on the oxide layer. Finally, we discuss the importance of each parameter, i.e. surface states, distributed impurity states, doping impurity states, thickness of oxide layer etc. on the log I versus applied potential characteristics. The present theory is also applicable for intimate contact, i.e. metal-semiconductor contact, crystalline material structures or for Schottky barriers in insulators or polymers.
Keywords: Amorphous materials; Current voltage characteristics; Electric currents; Fermi level; Semiconductor doping; Image force effects; Schottky barrier diodes